Observing landslide occurrence by GIS approach - Mokhtar, M.R.M. (2013)
There are many approaches in monitoring landslide but close range photogrammetry (CRP) provides mapping achieved almost immediately at a low cost compared with other approach.CRP is a dimension technology which is used to acquire 3D spatial information on objects in inaccessible areas. The method involves camera calibration which includes a process of finding the true parameters of the camera. The information is obtained through accurate assessment and used to create a 3D model which would be used for monitoring technique applications. In this study, calibration of the digital camera was performed using PhotoModeler Pro 5. A good calibration will have many points marked. Field observations on site survey were carried out on 6/11/2010 and 3/8/2011 over a monitoring area in Parit, Seri Iskandar, Perak. The landslide can be detected by calculation of two different epoch data achieved from Digital Elevation Models (DEMs) generation. The paper focuses on the monitoring on the studied area based on DEM area and volume generated from 3D surface analysis. Â© 2013 IEEE.